2020
DOI: 10.3390/ijerph17062048
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Nasopharyngeal Stenosis Correction Using a Modified Palatal Flaps Technique in Obstructive Sleep Apnea (OSA) Patients

Abstract: Background: Acquired nasopharyngeal stenosis is a rare and heterogeneous pathological condition that has different causes, generally resulting as a complication of a pharyngeal surgery, especially in patients affected by obstructive sleep apnea (OSA). Different approaches have been proposed for the treatment of nasopharyngeal stenosis but a unique and standardized management has not yet been presented. The aim of our paper is to evaluate the efficacy of our surgical technique, describing its steps and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Severe cases of NPS (grade 3) were not detected in the current study because they are much far less encountered than other grades [16,18].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Severe cases of NPS (grade 3) were not detected in the current study because they are much far less encountered than other grades [16,18].…”
Section: Discussioncontrasting
confidence: 56%
“…In the current study, 3 cases of the included NPS were caused by adenotonsillectomy. This could be attributed to some risk factors such as excessive mucosal removal, keloid tendency, existence of concomitant nasopharyngeal inflammation, and an extreme surgical electrocautery use [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this, a varied technique to bivalved palatal transposition flaps was used. This study also described promising results with none of the patients showing follow-up complications [6]. A study in Kenya documented the successful treatment of NPS using a facial artery Musculo mucosal flap as an alternative [7].…”
Section: Journal Of Endocrinology and Thyroid Researchmentioning
confidence: 59%
“…There are many surgical procedures proposed for the treatment of OSA. Surgery of the velo-pharyngeal region had a huge evolution going from ablative techniques (UP3 and LAUP) to remodeling techniques of the pharyngeal lateral walls [ 18 , 19 , 20 , 21 ]. In this scenario, barbed reposition pharyngoplasty (BRP), devised by Vicini et al [ 22 ], showed excellent outcomes at short- and long-term follow-up [ 23 , 24 ].…”
mentioning
confidence: 99%